O RPG (Role Playing Game) solo como alternativa didática ao ensino de Química - SARMENTO, James Valente (2023)
Games have always been part of humanity since there are records and have been applied to teaching since antiquity in Rome with soldiers and children. Nowadays we have some difficulties when teaching chemistry in schools. The reasons range from the lack of structure to the students' lack of interest in the subject. In this way, games provide a didactic alternative for educators and students, being a more dynamic, interesting and fun way to be applied in the classroom. Using Ausubel's theory of education, highlighting the subsumer concept and the meaningful material to have meaningful learning, it was possible in this work to propose a Solo RPG game to be used in the classroom, which also has the objective of serving as a theoretical support and inspiration to implement this teaching tool in schools. This method has already shown itself to be quite efficient, and its benefit has been reported by several authors today.